La gamificación para las enseñanzas de las matemáticas de operaciones con fracciones - Betun Rigchac, Luis Humberto; Torres Espinoza, Sleyder Alexander (Machala, 2021)
The development of this project seeks to determine the importance of the use of gamification in the subject of mathematics to develop new skills and abilities in students in the seventh year parallel "C" in the educational unit "Zoila Ugarte de Landívar" period 2021, In order to establish the importance of this pedagogical alternative in the academic training of students. The academic performance of the students before and after the application of gamification with didactic strategy was established and evaluated, and it was determined that students need the application of didactic dynamics and games, to experience a high level in their development of learning of mathematics, with an increase in their logical thinking, active participation in classes and a greater retention of the knowledge imparted by the teacher. In addition, these investigative antecedents gave rise to achieving the objectives set during the structuring of the project, which consisted of determining the impact generated by gamification for the teaching of operations mathematics with fractions in the students of the seventh year parallel "C" in the unit educational "Zoila Ugarte de Landívar" period 2021. The importance of this type of research that seeks to improve the development of teaching learning in educational institutions was determined, highlighting the use of these pedagogical alternatives, the gamification of learning is without place to doubts the main link that teachers must have to ensure that their students have meaningful, interactive, didactic, dynamic, quality and equal learning.
El desarrollo del presente proyecto busca determinar la importancia de la utilización de la gamificación en la asignatura de las matemáticas para desarrollar destrezas y habilidades nuevas en los estudiantes de séptimo año paralelo “C” en la unidad educativa "Zoila Ugarte de Landívar" período 2021, para de esta manera establecer la importancia de esta alternativa pedagógica en la formación académica de los alumnos. Se establecieron y evaluaron los rendimientos académicos de los estudiantes antes y después de la aplicación de la gamificación con estrategia didáctica, y se determinó que los estudiantes necesitan de la aplicación de dinámicas y juegos didáctico, para experimentar un alto nivel en su desarrollo del aprendizaje de las matemáticas, con un incremento en su pensamiento lógico, participación activa en clases y una mayor retentiva de los conocimientos impartidos por el docente. Además, estos antecedentes investigativos dieron cabida a alcanzar los objetivos planteados durante la estructuración del proyecto que consistía en determinar el impacto que genera la gamificación para la enseñanza de las matemáticas de operaciones con fracciones en los estudiantes de séptimo año paralelo “C” en la unidad educativa "Zoila Ugarte de Landívar" período 2021. Se determinó la importancia de este tipo de investigaciones que buscan mejorar el desarrollo de la enseñanza-aprendizaje en las instituciones educativas, resaltando la utilización de estas alternativas pedagógicas, la gamificación del aprendizaje es sin lugar a duda el nexo principal que deben poseer los docentes para asegurar que sus alumnos tengan un aprendizaje, significativo, interactivo, didáctico, dinámico, de calidad e igualdad.
Keywords: GAMIFICACION; EDUCACION; APRENDIZAJE; PEDAGOGIA; DESARROLLO